ChemInform Abstract: (S)‐Selective MenD Variants from Escherichia coli Provide Access to New Functionalized Chiral α‐Hydroxy Ketones. Issue 25 (3rd June 2013) - Westphal, Robert; Waltzer, Simon; Mackfeld, Ursula; Widmann, Michael; Pleiss, Juergen; Beigi, Maryam; Mueller, Michael; Rother, Doerte; Pohl, Martina
Abstract The first MenD variants from E.